Porn videos as evidence of adultery: a comparative study of Indonesian criminal law and Islamic law - Kurniawan, Kukuh Dwi (Legality : Jurnal Ilmiah Hukum, 2022)
Adultery is one of the categories of crimes that are prohibited under Indonesian law and is also categorized as a major sin according to Islamic law. With so many porn videos circulating through social media or the internet, the question of what if porn videos are used as evidence in court so that they can prosecute adulterers is raised. The purpose of this study is to find video criteria that can be used as legal evidence according to Islamic law and Indonesian Criminal Law. This study aims to find video criteria presented as legal evidence according to Indonesian criminal law and Islamic law so that it can be used as a reference for reforming Indonesian criminal law. This research was conducted by comparing Indonesian criminal law and Islamic law regarding video criteria as evidence of adultery. The results of this study found that according to Indonesian criminal law, because of the Constitutional Court's Decision No. 20/PUU-XIV/2016 there are limitations on videos that can be used as evidence in court, namely the method of acquisition must be in accordance with applicable legal rules. Meanwhile, according to Islamic criminal law, videos can be used as evidence of qorinah or instructions, but materially the content of the video contains the entry of almurd into the mikhalah. Based on these findings, the adultery video can be used as legal evidence, it can be referred to base on Islamic law by positioning it as evidence of guidance, and although qoth'i there must be four men as witnesses on charges of adultery.